2017
DOI: 10.1136/injuryprev-2017-042518
|View full text |Cite
|
Sign up to set email alerts
|

Cluster randomised control trial for cricket injury prevention programme (CIPP): a protocol paper

Abstract: BackgroundInjury prevention programmes (IPPs) are effective in reducing injuries among adolescent team sports. However, there is no validated cricket-specific IPP despite the high incidence of musculoskeletal injuries among amateur cricketers.ObjectivesTo evaluate whether a cricket injury prevention programme (CIPP) as a pretraining warm-up or post-training cool-down can reduce injury rates in amateur cricket players.MethodsCIPP is a cluster randomised controlled trial which includes 36 male amateur club teams… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 69 publications
(41 reference statements)
0
8
0
Order By: Relevance
“…Mean warm-up is 20±5.5 minutes, which is adequate as per Soomro et al 6 But we observed that the quality of training is not adequate and needs to be addressed. A posttraining cool-down is not being followed properly in the academies we studied.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…Mean warm-up is 20±5.5 minutes, which is adequate as per Soomro et al 6 But we observed that the quality of training is not adequate and needs to be addressed. A posttraining cool-down is not being followed properly in the academies we studied.…”
Section: Discussionmentioning
confidence: 49%
“…Soomro et al says CIPP as pretraining warm-up and post-training cool-down will result in significant reductions in Injury rates compared to the control group. 6 The average months of training in a year is 10.9±1.2 which is more than that observed in study by Noorbhai et al i.e. 7.6±2.7.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…It is a common perception that cricket is a nonimpact sport associated with fewer injuries than other sports. However, the literature shows that when injuries are measured in terms of injury rates (ie, per hour of athletic exposure), junior and amateur cricketers have higher rates of injury than professional cricketers [38], and injury rates are comparable to other noncontact or quasi-contact team sports such as soccer, basketball, and tennis [39]. In recent times, the use of mHealth and Web-based technology to monitor an athlete’s health is becoming an important component of sports medicine [5].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, medical experts and physiotherapists recommend slow and progressive loading of the MSK system to reduce the risk of avulsion or overuse type injuries. 19,20 A similar approach has been used in cricket where Australian and English & Wales Cricket Boards have age-specific fast bowler workload guidelines 21,22 that are a part of the coach training programmes and are taken as standard to monitor the training of junior fast bowlers. However, there is a lack of published data on adherence to bowling workload guidelines in community cricket.…”
Section: Introductionmentioning
confidence: 99%